2013
DOI: 10.1021/ol4012986
|View full text |Cite
|
Sign up to set email alerts
|

Unique Reactivity of anti- and syn-Acetoxypyranones en Route to Oxidopyrylium Intermediates Leading to a Cascade Process

Abstract: Unique reactivity of anti- and syn-acetoxypyranones was observed in oxidopyrylium-alkene [5 + 2] cycloadditions. The subtle interplay between the corresponding acetoxypyranone conformation and steric bulk of tertiary amine bases causes syn-acetoxypyranones to undergo [5 + 2] cycloaddition appreciably faster than anti-acetoxypyranones. Additionally, the efficiency of a cascade process that afforded a novel tetracyclic lactol was determined to be dependent on the relative stereochemistry of each diastereomer, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…3 Specifically, oxidopyrylium-alkene [5+2] cycloadditions readily afford bridged, polycyclic ethers 4 similar to those found in biologically active natural products. 5 In our previous report, 6 we observed differing reactivity of anti-and syn-acetoxypyranones 1 toward presumed oxidopyrylium-alkene intermediates en route to [5+2] cycloadditions (Scheme 1a). 7 Herein, we report the synthesis of several novel caged ring systems 4 obtained via oxidopyrylium-alkene [5+2] cycloaddition conjugate addition cascade (C 3 ) sequences derived from acetoxypyranone-alkenes 2 with pendant nucleophiles (Scheme 1b).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…3 Specifically, oxidopyrylium-alkene [5+2] cycloadditions readily afford bridged, polycyclic ethers 4 similar to those found in biologically active natural products. 5 In our previous report, 6 we observed differing reactivity of anti-and syn-acetoxypyranones 1 toward presumed oxidopyrylium-alkene intermediates en route to [5+2] cycloadditions (Scheme 1a). 7 Herein, we report the synthesis of several novel caged ring systems 4 obtained via oxidopyrylium-alkene [5+2] cycloaddition conjugate addition cascade (C 3 ) sequences derived from acetoxypyranone-alkenes 2 with pendant nucleophiles (Scheme 1b).…”
mentioning
confidence: 86%
“…Despite attempts to isolate aldehyde 3a, acetoxypyranoneenal 2a delivered lactol 4a (Scheme 3). 6 The spontaneous nature of the concave conjugate addition led us to further probe these reaction sequences. Investigation of stepwise variants revealed fundamental information toward the development of the oxidopyrylium-alkene [5+2] C 3 .…”
mentioning
confidence: 99%
“…As part of our research program directed toward [5+2] cycloadditions, [78][79][80][81][82][83][84] we explored mechanistic pathways of acetoxypyranone-derived oxidopyrylium species en route to [5+2] cycloadditions [81] that led to the discovery of polycyclic ether-benzopyran 4 (Scheme 1). Commercially available aldehyde 2 was treated with 2-furyllithium to provide the desired alcohol (not shown) in quantitative yield.…”
Section: Previous Synthesis Of Polycyclic Ether-benzopyranmentioning
confidence: 99%
“…Mitchell and coworkers have extensively studied the intramolecular cycloaddition chemistry with acetoxypyrones, focusing on features such as the choice of base as well as the stereochemistry of the tether. 33 When separately running cycloadditions on molecules where the tether and the acetoxy groups were either anti ( 21.1 ) or syn ( 21.2 ) to one another, it was revealed that the syn isomer underwent cycloaddition chemistry faster than the anti (Scheme 21). This is believed to be due to the orientation of the proton in relationship to the acetoxy group, which would create added sterics to the deprotonation event.…”
Section: Oxidopyrylium Ylides Through Acetoxypyrone Eliminationmentioning
confidence: 99%
“…During the course of these studies, the group found that that when the resulting products contained an aldehyde, hemiacetal 1,4-addition products were observed. 33 A subsequent survey of tethered alkenes substituted with various potential nucleophilic groups led to a series of new multicyclic and stereochemically dense compounds (Scheme 22). 34 Anti -acetoxypyranoses were used for the cycloadditions due to their relative abundance when compared to the syn .…”
Section: Oxidopyrylium Ylides Through Acetoxypyrone Eliminationmentioning
confidence: 99%